IMPLEMENTASI PROJECT BASED LEARNING (PjBL) BERPENDEKATAN SCIENCE EDUTAINMENT TERHADAP KREATIVITAS PESERTA DIDIK - Ardianti, Sekar Dwi; Pratiwi, Ika Ari; Kanzunnudin, Mohammad (Universitas Muria Kudus, 2017)
The development of science and technology gives effect to the development of human resources. Education has a decisive role for the development and realization of human resources according to the demands of the times. One of the basic education that should be mastered by students is a science because science can not be separated from everyday human life. Science as the proceedings applies the scientific method to solve problems and discover new concepts. In the process of inquiry or discovery are required special skills in thinking and acting. One of the capabilities that need to be developed is the ability of students to think creatively. This study was aimed at examining the effect of the the project based learning by science edutainment approach on students creativity. This study used the post-test control group design. This study used cluster random sampling to devide samples into two groups. The experimental group was implemented model of project based learning by science edutainment approach and the control group was implemented conventional method. The independent variables in this study are the type of learning method and dependent variable is the students creativity. The average of students creativity score in experimental group is 7,52 and 6,78 for control group. The t-test showed a significantly different students creativity, between the experimental and control groups. The use of project based learning by science edutainment approach significantly influenced the students creativity